Zinc Removal From The Industrial Wastewater Using Activated Carbon Synthesized From Mangrove - Samsudin, Nur Fitri Syafiqah (Universiti Sains Malaysia, 2021)
Most of wastewater effluent contains dangerous heavy metals that must be appropriately handled. Heavy metal pollution is a serious problem in developing countries, as most industrial operations have increased heavy metal contamination in lakes, rivers, and other water sources. Thus, a substantial amount of research has been performed on low-cost adsorbents to examine their potential in heavy metal removal. As a result, a summary and assessment of mangrove as a low-cost adsorbent have been completed in this report. This study assesses the potential of activated carbon derived from mangroves for the removal of a specific heavy metal, zinc. Aside from that, the examination of the key factors that impact heavy metal removal, which are the effect of temperature, initial concentration, and contact duration on heavy metal removal, is also being examined. The adsorption capacity increased with the increase of initial concentration of Zn2+ from 1 ppm to 7 ppm resulted in an increase in adsorption capacity from 0.1604 mg/g to 1.1627 mg/g. As the temperature raised from 30°C to 60°C, the adsorption capability of Zn2+ were decreased indicating the process was exothermic. The capacity for Zn2+ adsorption reduced from 1.241 mg/g to 1.1627 mg/g as the temperature increased. For adsorption isotherm model, Freundlich isotherm model at temperature of 60°C is more suitable to describe Zn2+ adsorption on mangrove activated carbon due to higher correlation coefficient, R2value at 0.5984. The correlation coefficient, R2from the pseudo-second order model for Zn2+ adsorption was 0.9959 which is higher than pseudo-first order model, 0.9695. This indicate that pseudo-second order is more suitable more kinetic adsorption model for Zn2+ adsorption.